Novel, gain-flattened L-band EDFA with ASE utilization with > 40 nm 3 dB bandwidth - Adikan, Faisal Rafiq Mahamd; Mahdi, M.A.; Thirumeni, S.; Poopalan, Prabakaran; Dimyati, Kaharudin; Ahmad, Harith (John Wiley & Sons, 2001)
A simple gain-flattened L-band erbium-doped fiber amplifier (EDFA) is demonstrated, utilizing unwanted C-band amplified spontaneous emission (ASE) to enhance L-bulld gain performance. An L-band flat gain range of 50 nm (1560-1610 nm) is achieved for use in wavelength-division multiplexing (WDM) transmission systems. Gain flatness with a 3 dB gain discrepancy is obtained through manipulation of the pump power. (C) 2001 John Wiley & Sons, Inc.